Skeletal stem/progenitor cells provide the niche for extramedullary hematopoiesis in spleen - O’Neill, Helen C.; Lim, Hong Kiat (Frontiers in Physiology, 2023)
In bone marrow, the niche which supports hematopoiesis and nurtures hematopoietic stem cells (HSCs) contains perivascular reticular cells representing a subset of skeletal stem/progenitor cells (SSPCs). These stromal cells which provide the niche are lost or become inadequate during stress, disease or ageing, such that HSCs leave bone marrow and enter spleen and other peripheral sites to initiate extramedullary hematopoiesis and particularly myelopoiesis. Spleen also maintains niches for HSCs under steady-state conditions, evident since neonatal and adult spleen contain HSCs in low number and provide low-level hematopoiesis. In spleen, HSCs are found in the sinusoidal-rich red pulp region also in the vicinity of perivascular reticular cells. These cells resemble to some extent the known stromal elements reflecting HSC niches in bone marrow, and are investigated here for their characteristics as a subset of SSPCs. The isolation of spleen stromal subsets and the generation of cell lines which support HSCs and myelopoiesis in vitro has led to the identification of perivascular reticular cells which are unique to spleen. Analysis of gene and marker expression, as well as differentiative potential, identifies an osteoprogenitor cell type, reflective of one of several subsets of SSPCs described previously in bone, bone marrow and adipose tissue. The combined information supports a model for HSC niches in spleen involving perivascular reticular cells as SSPCs having osteogenic, stroma-forming capacity. These associate with sinusoids in red pulp to form niches for HSCs and to support the differentiation of hematopoietic progenitors during extramedullary hematopoiesis.